2019
DOI: 10.1097/acm.0000000000002701
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary, Multi-Institution Telehealth Course for Third-Year Medical Students

Abstract: Problem The American Medical Association has called for telehealth to become a core competency of medical students. Studies indicate that a principal reason physicians do not practice telehealth is lack of training, yet patient interest in and satisfaction with telehealth are high. No comprehensive U.S. undergraduate medical education curriculum teaching telehealth principles has been published. Approach In February 2018, the Uniformed Services Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 4 publications
3
72
0
Order By: Relevance
“…We felt that we were able to accomplish our goal of creating a useful opportunity for medical students to develop their clinical skills in the setting of social distancing. This runs consistent with previous studies which have shown that medical students find telehealth education interesting, clinically useful, and a good use of their time, in both primary care and sub-specialty settings (Dzara et al, 2013;Jonas et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…We felt that we were able to accomplish our goal of creating a useful opportunity for medical students to develop their clinical skills in the setting of social distancing. This runs consistent with previous studies which have shown that medical students find telehealth education interesting, clinically useful, and a good use of their time, in both primary care and sub-specialty settings (Dzara et al, 2013;Jonas et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Feedback was given in a visible, yet less structured way than may otherwise be when evaluating more common skills, physical exam, etc. A checklist, such as that proposed by Jonas et al could be a valuable tool to standardize the evaluation of telehealth, and to make uniform the quality of each encounter [ 11 ]. The post-assessment will further characterize feedback structure and medical student satisfaction with its quality, and may give further support for telehealth as a way to more actively engage learners and educators.…”
Section: Discussionmentioning
confidence: 99%
“…These students participated in this clinic from mid-April 2020 through the end of May 2020, encompassing the greatest peak of COVID-19 cases in Detroit. Published studies to date regarding telehealth training for medical students had commonly used pre- and post-tests or surveys, in addition to qualitative feedback, as a means to track student interest in and skill with telehealth [ 3 , 11 ]. As such, a pre-assessment based on these studies was designed, distributed as an email, and collected through WSU Qualtrics.…”
Section: Methodsmentioning
confidence: 99%
“…26 They could use the following learning vehicles to help medical students explore these domains: (1) asynchronous lectures covering telehealth history; (2) discussions on applications, ethics, safety, etiquette, and patient considerations; (3) faculty-supervised standardized patient telehealth encounters; and (4) hands-on diagnostic or therapeutic procedures using telehealth equipment such as live video, the store-and-forward method, remote patient monitoring (RPM), and mobile health. 26 , 27 Telemedicine’s applications are abundant and we will focus on how medical schools can consider formalizing the medical student exposure in 4 key areas: (1) telesurgery, (2) telerehabilitation, (3) tele-intensive care units (tele-ICUs), and (4) chronic disease management and RPM.…”
Section: Telemedicine In Medical Educationmentioning
confidence: 99%